Pengaruh Motivasi Belajar Terhadap Prestasi Belajar Matematika Siswa Kelas VIII SMPN 1 Kuala Behe - winata, rahmat; Friantini, Rizki Nurhana (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2019)
The purpose of this study was to determine the effect of learning motivation on mathematics learning achievement of eighth grade students of SMP N 1 Kuala Behe acedemic year of 2018/2019 Landak Regency. This type of research was quantitative with ex post facto approach. The population of all eighth grade students at SMP N 1 Kuala Behe. The number of sample in this study was 64 students who were selected using saturated sampling technique. The data analysis technique used simple linear regressionwith prerequisite test namely normality of Kolmogorov-Smirnov method, heteroscedasticity of Glejser method, linearity using test for linearity, multicolonity using Variance Inflation Factor (VIF), and autocorrelation of Durbin-Watson method. The result shows that there is an effect of learning motivation on mathematics learning achievement of eighth grade students of SMP N 1 Kuala Behe academic year 2018/2019 Landak Regency. The result of R square = 0,915 x 100% = 19,5% which indicates that the mathematics learning achievement of eighth grade students of SMP N 1 Kuala Behe can be explained by learning motivation of 19,5%.